Development of SCC with crushed rock fines as filler - Girish, S.; Arjun, H. R. (Journal of Structural Engineering, 2024)
The use of Crushed Rock Fines (CRF) in SCC is very uncommon. Also, particles of CRF are very angular, flaky and inert. Casting SCC using this marginal material is an interesting and an important issue for sustainable development. In this study, a new mixture proportioning method based on absolute volume concept starting with a volume of paste(Vp) (range 0.38 to 0.43) was adopted which reduced the number of trials to fabricate SCC. The cement contents 300, 360, 390 and 450 kg/m³ were used with a constant water content of 215 l/m³. Cubes of 150 mm were cast and tested for compressive strength. Higher paste content not only makes the mix cohesive but also increases the slump flow (reduces yield stress) and compressive strength. However an optimal value is reached at a particular value of Vp (0.41), thus highlighting the importance of volume of paste in the mix design. Further, SCC specimen showed higher 28 days compressive strength when compared with normal concrete indicating superiority of SCC even with filler like CRF.